Driving Employee Performance: Exploring Job Stress as A Key Mediator in Employee Effectiveness in a Procurement Company - Puspitasari, Nawar Tri; Anwar, Muhadjir (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This study aims to examine the mediation of work stress on the influence of job demands and turnover intention on employee performance at PT. Empat Putera Utama Bersama Surabaya. The research material is based on the problem of high job demands from the company due to the large demand from the company's clients. On the other hand,turnover intentionis one of the serious problems in the company that requires further evaluation.The method used is quantitative with an approach explanatory research. This method is used because this study will explain the position of each variable and the influence between one variable and another. The study was conducted using a survey method with data collected through a questionnaire. The population in this study included employees and superiors of PT. Empat Putera Utama Bersama, with samples taken through a saturated sampling technique of 55 employees. The analysis was carried out using SEM-PLS. The findings of this study show that high job demands can increase employee motivation and performance if managed well. Employees withturnover intentionkeep trying to work optimally to leave a good impression and achieve targets. Job stress mediates the relationship between job demands and performance, because environmental support helps employees manage stress. Job stress does not mediate turnover intentionand performance, because external factors have more influence, while a supportive work environment keeps employees engaged